PENGARUH DISIPLIN KERJA DAN PENEMPATAN PEGAWAI TERHADAP PRESTASI KERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN KUTAI TIMUR - Titin Ruliana, Lempung, Theresia Militina (EKONOMIA, 2016)
The purpose of this study is to analyze and determine the influence of labor discipline and staffing of the secretariat employee job performance East Kutai Regency and analyze the variables that give dominant influence on the performance of employees of the Secretariat East Kutai Regency.The theory used in this research is the theory of labor discipline, staffing and work performance. The population in this study were all employees in the Secretariat of the East Kutai Regency with a sample of 80 people taken randomly. While the research instrument was a questionnaire and model of data analysis used is multiple linear regression. Testers hypothesis using F test and t test.Research shows that a strong influence of variables and variable working Discipline staffing to the work performance of employees in the Secretariat of the East Kutai Regency. Based on the analysis of work performance of employees in the Secretariat of the East Kutai Regency obtained correlation coefficient (R) of 0.624 including a strong relationship category. Value of determination (R2) of = 0.405, this means working Discipline variables and variables may explain the variable staffing Work performance of employees amounted to 40.5%, while the remaining 59.5% is explained by other variables not examined in this study. Furthermore, from the F test obtained Fhitung = 20.206 with significant numbers because the probability 0.000 0.000 less than 0.05, the regression model can be used to calculate the employee's job performance or it can be said that the Disciplinary variables and variable staffing work together affect the work performance Secretariat employees in East Kutai Regency.